Pair microteaching:an unrealistic pedagogy in pre-service methodology courses?. Issue 2 (15th March 2017) - Yan, Chunmei; He, Chuanjun
Abstract: Despite its inherent nature of artificiality, microteaching has been widely used as a routine procedure in pre-service teacher education courses to apply theoretical knowledge and develop practical teaching competence. Its importance in the practice element of teacher education programmes has given rise to a considerable amount of attention to its potential in research. However, there has been little or no research on pair microteaching, which is exploited as a circumstantial compromise and innovation. This article reports on a small-scale study of the effect of pair microteaching on EFL (English as a foreign language) student teachers' professional learning. Triangulated sources of data were collected qualitatively to investigate a group of 30 student teachers' perspectives about their eight-week-long microteaching experience on an English language teaching methodology course. The results show a high level of endorsement of the experience despite the drawbacks of limited practice opportunity and artificiality of the experience. The article concludes that pair microteaching can be a feasible pedagogy in methodology courses that can be supplemented by other forms of direct and indirect school experiences.